Deciphering different effects of ZVI and NaOH on metabolic characteristics in the process of methanogenesis recovery from VFA suppression. (15th June 2023) - Niu, Jianan; Kong, Xin; Li, Qingxia; Zhang, Yongmei; Yuan, Jin; Liu, Jianguo; Zhang, Yifeng
Abstract: Dosing zero valent iron (ZVI) or sodium hydroxide (NaOH) is the common method of addressing acidification in anaerobic digestion (AD) systems; however, few studies have discussed and compared their effects on microbial metabolism. In the present study, microbial syntrophy and metabolic pathways under ZVI and NaOH regulation are comparatively analyzed through microbial network analysis and metagenomic/metaproteomic analyses. CH4 yield in the ZVI reactor was 414 mL/gVS, an increase of 23% when compared with that in the reactor with NaOH dosing (336 mL/gVS). The methanogenesis recovery period in the ZVI reactor (37 days) was shorter than that in the NaOH reactor (48 days). Co-occurrence networks indicated that ZVI promoted Methanoculleus and Methanosarcina to establish a complex syntrophic association with SAO bacteria ( Syntrophaceticus and Aminobacterium ) and syntrophic acetogens ( Syntrophomonas ), strengthening SAO-hydrogenotrophic methanogenesis (HM) and acetoclastic methanogenesis (AM) pathways simultaneously. Metagenomic analysis showed that the relative abundance of mcrA and fwdB in the ZVI reactor was higher 27% than that in the NaOH reactor. Furthermore, through metaproteomics analysis, much more enzymes related to glucose degradation, bioconversion of butyric acid and pyruvate, conversion of formate and acetate to CO2, and production of CH4 from acetate and CO2 were significantly upregulated under ZVI regulation than under NaOH regulation (fold change relative to control [FC] > 1.5, p  < 0.05). The results of the present study enhance our understanding of methanogenic mechanisms under the regulation of ZVI, providing a theoretical basis for its practical application in AD systems experiencing VFA suppression. Graphical abstract: Image 1 Highlights: CH4 yield of ZVI reactor increased by 23% compared to that of NaOH reactor. ZVI, NaOH enhanced syntrophic acetate oxidation and hydrogenotrophic methanogenesis. ZVI increased relative abundance of mcrA and fwdB by 27% compared to NaOH. ZVI promoted acetoclastic methanogenesis dominated by Methanosarcina . Metabolic enzymes in AD significantly upregulated by ZVI regulation.